Wireless Fire Alarm System in Power Plant - Andri Gautama Suryabrata; Tatang Mulyana; Deden Witarsyah (IAES Indonesia Section, 2015)
This paper presents a wireless fire alarm system inpower plant. In the wireless fire alarm system had two sensorslike smoke sensor and temperature sensor. The smoke sensor isdetected the smoke when during the fire disaster happens. Thefire disaster happens the temperature will increase to above 650Call the wire will burnt and will getting smoke around the room.When the smoke sensor and the temperature sensor had signalwill pass through to microcontroller PIC18F4550 and send thedata to computer with using X-bee Pro device. The X-bee Prowill receive signal to computer and show in the Visual Basicabout the status of the room and the temperature at the room.